Iddah Dalam Al-Qur’an: Kajian Tafsir Atas Dimensi Perlindungan Dan Kehormatan Perempuan - Sutrawati Sutrawati; Basri Mahmud; Mukhtar Mukhtar (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2026)
The matter of ‘iddah is often viewed merely as a normative obligation without uncovering its underlying philosophical dimensions, particularly those related to the protection and dignity of women after divorce or the death of a husband. The background of this study lies in the gap between the Qur’anic text (das sollen), which stipulates a waiting period, and social reality (das sein), which often perceives ‘iddah as a burden or a restriction on women’s activities. This research aims to examine the Qur’anic verses on ‘iddah using a thematic exegesis (mawḍū‘ī) approach in order to analyze its embedded dimensions of psychological, social, and biological (lineage) protection. The method employed is qualitative research based on library studies, utilizing content analysis of primary sources (the Qur’an and authoritative tafsir works) as well as secondary literature. The main findings show that the stipulation of ‘iddah in the Qur’an—such as in Q. al-Baqarah 2:228 and al-Ṭalāq 65:4—constitutes a legal mechanism that is pro-women, as it holistically safeguards lineage clarity, provides space for emotional recovery after trauma, and affirms the dignity of women as respected legal subjects. This study emphasizes that ‘iddah is not merely a ritual obligation but a form of shar‘i instrumentation that functions to preserve the purity of lineage while reinforcing women’s honor against stigma or negative social perceptions.